Habitual entrepreneurs: Possible cases of entrepreneurship addiction? - Spivack, April J.; McKelvie, Alexander; Haynie, J. Michael (Journal of Business Venturing, 2014)
We examine the underlying psychological processes that may motivate habitual entrepreneurs to engage in entrepreneurship repeatedly. By drawing on the psychology literature on behavioral addictions, such as workaholism and Internet use, we develop a framework that defines the symptomatology of what we identify as a “behavioral addiction to entrepreneurship.” Through interviews with two habitual entrepreneurs, we demonstrate how these addiction symptoms manifest in the entrepreneurial context. We also demonstrate how psychological, emotional, and physiological aspects of the entrepreneurial experience reinforce a behavioral addiction to entrepreneurship. Our theorizing offers insights into the psychological origins of repeated engagement in venture creation activities and yields insights into possible “dark side” of entrepreneurship outcomes.